MANAGEMENT OF RETINAL HEMANGIOBLASTOMA IN VON HIPPEL-LINDAU DISEASE - Wiley, Henry E; Krivosic, Valerie; Gaudric, Alain; Gorin, Michael B; Shields, Carol; Shields, Jerry; Aronow, Mary E; Chew, Emily Y (Retina (Philadelphia, Pa.), 2019)
To review the current state of diagnosis and management of retinal hemangioblastoma and retinal vascular proliferation arising from von Hippel-Lindau (VHL) disease. A review of the literature was performed. Consensus was reached among authors regarding current practice, with reference to published data where possible. von Hippel-Lindau disease and its ocular manifestations are relatively rare, and there is limited evidence in the literature on which to base management. There was consensus on core principles, including 1) recognition and diagnosis of von Hippel-Lindau disease when present, with appropriate referral for care of this potentially lethal systemic condition; 2) regular ophthalmic evaluation for individuals with von Hippel-Lindau disease, to identify and offer timely treatment for new or active retinal hemangioblastomas; 3) ablative treatment of retinal hemangioblastomas that can be safely destroyed, to lower risk of vision loss; 4) observation or consideration of nonablative treatments for retinal hemangioblastomas that cannot be safely destroyed; and 5) observation of asymptomatic retinal vascular proliferation, with consideration of vitrectomy for lesions exerting effects on vision. Ocular outcomes can be gratifying in many cases with appropriate management. Improved understanding of the molecular basis for the disease creates an opportunity for rational design of better therapies.